(untitled) (Research, Society and Development, 2021)
This article aims to present the historical context of the Graduate Program in Education of the Faculty of Science and Technology of Universidade Estadual Paulista. It results from a scientific initiation research that aimed to investigate the history and academic production of the referred Program, prioritizing the critical analysis of the productions over the training of teachers of the early years. For this, an investigation with a qualitative approach was developed, through bibliographic research and documentary analysis. The bibliographic research (Lima & Mioto, 2017) consisted of focusing on the role of the public university in the Brazilian educational context and the training of teachers in early years. For the analysis of productions with PPGE/FCT/Unesp, we used documentary analysis (Cellard, 2010), seeking to build the “state of knowledge” of academic production. We understand that the university has an important role as a space for the production of knowledge and professional training, committed to the democratization of knowledge and, consequently, to the transformation of society in favor of social justice. The results showed that the creation of the Program occurred in 2000, initially with a master’s degree and, later, also a doctorate, focusing on human development and teacher training, with 327 dissertations and 89 theses having been completed in the period under analysis. The Program consists of 30 accredited professors and 554 enrolled students, 405 master’s and 149 doctoral students. We identified that the academic productions of PPGE/FCT/Unesp emphasize Basic Education and Higher Education and have, as a common and repeated aspect, the defense of teacher education as an essential element for improving the quality of teaching in public schools and, consequently, of practices pedagogical aspects of teachers as critical and reflective subjects.